Antiapoptotic properties of MALT1 protease are associated with redox homeostasis in ABC‐DLBCL cells. Issue 12 (26th September 2019) - Zhu, Leqing; Tang, Fen; Lei, Zhiwei; Guo, Chengbin; Song, Yueqi; Huang, Junqing; Xia, Xichun
Abstract: Mucosa‐associated lymphoid tissue lymphoma translocation protein‐1 (MALT1) protease presents crucial antiapoptotic properties in activated B cell‐like diffuse large B‐cell lymphoma (ABC‐DLBCL); however, the mechanism is unclear. Here, we reported that inhibition of MALT1 protease in ABC‐DLBCL cells led to cell apoptosis, along with elevated mitochondrial reactive oxygen species production and a reduced oxygen consumption rate. These alterations induced by MALT1 protease inhibition were associated with reduced expression of glutaminase (GLS1) and glutathione levels. We further show that MALT1 protease was required for the activation and nuclear translocation of c‐Jun, which functions as a transcription factor of the GLS1 gene by binding directly to its promoter region. Taken together, MALT1 protease maintained mitochondrial redox homeostasis and mitochondrial bioenergetics through the MALT1‐c‐Jun‐GLS1‐coupled metabolic pathway to defend against apoptosis in ABC‐DLBCL cells, which raises exciting possibilities regarding targeting of the MALT1‐c‐Jun‐GLS1 axis as a potential therapeutic strategy against ABC‐DLBCL.